County-Level Integrated Healthcare Practice in China: A Kaiser Permanente-Inspired Approach - Na Li; Yin Dong; Gaofeng Zhang (International Journal of Integrated Care)
Introduction: China’s rapidly aging population and rise in chronic diseases put immense strain on the country’s healthcare system. To address these challenges, Yuhuan People’s Hospital established County-level Integrated Health Organization (CIHO) as part of the Healthy China 2030 initiative. Description: Based on the Kaiser Permanente (KP) model, the CIHO takes a multi-disciplinary, collaborative approach to deliver integrated care. It brings together various medical specialties, collaborates with community organizations and companies, and implements reforms in information technology and payment models. Through these efforts, the CIHO has significantly improved healthcare delivery in Yuhuan county. Discussion: Population segmentation relies on data integration and segmentation tools to identify targeted healthcare needs. The allocation and collaboration of health workforce for residents with different health conditions are suggested to be dynamically designed according to both internal and external factors. Corresponding payment mechanism is also an important factor that needs to be taken into consideration. Conclusion: The CIHO’s success has provided a model for integrated, efficient healthcare that could be replicated in other regions of China and offer insights for rural areas in other countries facing similar demographic and epidemiological pressures.